Tecnología del habla y dificultades de comprensión linguística oral - Santiuste Bermejo, Víctor; Reyzábal Manso, María Isabel (Revista Complutense de Educación, 2005)
This paper deals with oral language comprehension and strategies listeners use to understand a discourse. Our subjects were secondary education students, and the experimental group showed language comprehension difficulties. Additionally we explain the first step on how the "reflex arc of artificial language comprehension" originates. To this purpose and thanks to Telefonica I+D’s collaboration, we have made use of new technologies, in particular, speech technology. Among the conclusions, the use of the same comprehension strategies by both groups of students stands out, and thus, it seems plausible that comprehension would be qualitatively equal in average individuals. We also verified that lack of memory and vocabulary emerge as key difficulties.